Configurações sócioculturais da docência no Instituto Médio de Economia de Cabassango, Cabinda/Angola - Andre Ndoqui Junior (2014)
The teacher working conditions are among the most discussed factors in all occasions when it comes to the improvement of education in Angola and whatever level of education considered. In this perspective, the research sought to understand the confronting the individual and collective differences in the school environment and outside of it, with the theme of Teaching Sociocultural Settings in the Middle Cabassango economy Institute, Cabinda-Angola. The notion of working conditions means the set of features that allow the accomplishment of the work, involving the physical facilities, materials and supplies available, equipment and means of carrying out the activities and other kinds of support necessary for the organisation of teaching work, as well as career teaching's plan, in short, the conditions experienced by teachers inside and outside the school environment. Was a need to identify what are the determinants that affect the teaching and learning process and make a ...The landmark of this investigation are sociocultural settings in teaching in consequences of socio-political, social, historical changes and reforms in various sectors that have occurred in the country in the period from 2000 to 2010. The development of quality research quantativa at the Institute of economy of Cabinda Cabassango Angola adopted as tools of data collection, observation, questionnaire and 182 6 semi-structured interview. The analyses carried out on the subject were based mainly on the following authors: MARX (2002). Tardif and Lessard (2005) Giddens (2002) MOSCOVICI (2003), (YUS, 1998) MOREIRA and CANDAU (2003), (FRANCO and BONAMINO 2005) (FR, 2003) (ASSUMPTION, 2008) (FOUCAULT, 1995 , 2007), (OLIVEIRA, 2004). among others. The results corroborate the hypothesis that the wear and tear of teachers is determined largely by the workload, nature of the activity, by the form of organization of their work, as well as the social devaluation of the teacher. However, even If most teachers demonstrate a favourable pedagogical practice in dealing with individual differences of students, it was evident the complexity of this issue in the everyday life of his practice, when dealing with cultural differences present in the school community, which is still a bottleneck to be diluted for the good of the community itself and especially for teaching and learning.